2004
DOI: 10.1381/096089204323093426
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cholecystokinin Levels after Vertical Banded Gastroplasty: Effects of an Acidified Meal

Abstract: VBG increases the peak of CCK secretion and shortens the time to reach it. These changes could contribute to the satiety effects of gastric restrictive operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…52,152,153 One study found that, 120 days after VBG, the plasma CCK response to an acidified meal was faster and with a higher peak than before surgery, though the total AUC was not different. 154 Ockander and coworkers 155 found an increased density of CCK cells in the duodenal mucosa of patients post-JIB, but the significance of this finding is not clear.…”
Section: Cholecystokininmentioning
confidence: 97%
“…52,152,153 One study found that, 120 days after VBG, the plasma CCK response to an acidified meal was faster and with a higher peak than before surgery, though the total AUC was not different. 154 Ockander and coworkers 155 found an increased density of CCK cells in the duodenal mucosa of patients post-JIB, but the significance of this finding is not clear.…”
Section: Cholecystokininmentioning
confidence: 97%
“…In some studies, lower fasting ghrelin levels were reported after laparoscopic sleeve gastrectomy (SG) [88,89]; while other findings showed increases in fasting ghrelin following LAGB [9092]. A rise in ghrelin concentrations following both AGB [93,94] and VGB [92,95,96], have been widely observed, but several studies have noted no change following either procedure [97100], and two cross-sectional studies found a reduction in ghrelin concentrations following AGB, in comparison to BMI-matched counterparts [101,102]. …”
Section: Interactions Between Gut Peptides and Brain Systems Relevmentioning
confidence: 99%
“…7 These effects are probably related to endocrine or paracrine effects of the operations. Vertical banded gastroplasty increases post-meal cholecystokinin plasma levels, 8 whereas Roux-en-Y gastric by-pass inhibits basal and post-prandial ghrelin plasma levels 9 and increases peptideYY (PYY) concentrations. 10 Jejuno-ileal by-pass increases cholecystokinin, motilin, glucagon-like peptide 1 and PYY, 11 delays gastric emptying and reduces hunger sensations.…”
Section: Introductionmentioning
confidence: 99%